Antifungal activity of propolis on different species of Candida - Ota, Claudia [UNESP]; Unterkircher, Carmelinda [UNESP]; Fantinato, Vera; Shimizu, M. T. (Wiley, 2001)
Propolis is a resinous material collected by bees from the buds or other parts of plants. It is known for its biological properties, having antibacterial, antifungal and healing properties. The antifungal activity of propolis was studied in sensitivity tests on 80 strains of Candida yeasts: 20 strains of Candida albicans, 20 strains of Candida tropicalis, 20 strains of Candida krusei and 15 strains of Candida guilliermondii. The yeasts showed a clear antifungal activity with the following order of sensitivity: C. albicans > C. tropicalis > C. krusei > C. guilliermondii. Patients with full dentures who used a hydroalcoholic propolis extract showed a decrease in the number of Candida.
Keywords: Antifungal activity; Candida; Denture stomatitis; Propolis; propolis; adult; antibiotic sensitivity; antifungal activity; Candida albicans; Candida guilliermondii; Candida krusei; Candida tropicalis; clinical article; colony forming unit; controlled study; denture; human; minimum inhibitory concentration; mouth hygiene; nonhuman; priority journal; saliva; stomatitis; Antifungal Agents; Humans; Microbial Sensitivity Tests; Plant Extracts; Stomatitis; Stomatitis, Denture; Apoidea; Issatchenkia orientalis; Pichia guilliermondii